Auxin and Gibberellins Are Required for the Receptor-Like Kinase ERECTA Regulated Hypocotyl Elongation in Shade Avoidance in Arabidopsis - Du, Junbo; Jiang, Hengke; Sun, Xin; Li, Yan; Liu, Yi; Sun, Mengyuan; Fan, Zhou; Cao, Qiulin; Feng, Lingyang; Shang, Jing; Shu, Kai; Liu, Jiang; et al. (Frontiers in Plant Science, 2018)
Plants use shade avoidance strategy to escape the canopy shade when grown under natural conditions. Previous studies showed that the Arabidopsis receptor-like kinase ERECTA (ER) is involved in shade avoidance syndrome. However, the mechanisms of ER in modulating SAR by promoting hypocotyl elongation are unknown yet. Here we report that ER regulated hypocotyl elongation in shade avoidance requires auxin and gibberellins (GAs). The T-DNA insertional ER mutant er-3 shows a less hypocotyl length than that in Col-0 wild type. Promoter::GUS staining analysis shows that ER and its paralogous genes ERECTA-LIKE1 (ERL1) and ERECTA-LIKE2 (ERL2) are differentially expressed in the seedlings, of which only ER is most obviously upregulated in the hypocotyl by shade treatment. Exogenous feeding assay by using media-application with vertical-grown of Arabidopsis seedlings showed that the hypocotyl length of er-3 is partially promoted by indol-3-acetic acid (IAA), while it is relatively insensitive of er-3 to various concentrations of IAA than that of Col-0. Hypocotyl elongation of er-3 is promoted similar to that of Col-0 by high temperature in the white light condition, but the elongation was not significantly affected by the treatment of the auxin transport inhibitor 1-N-naphthylphthalamic acid (NPA). Exogenous GA3 increased the hypocotyl elongation of both er-3 and the wild type in the shade condition, and the GA3 biosynthesis inhibitor paclobutrazol (PAC) severely inhibits the hypocotyl elongation of Col-0 and er-3. Further analysis showed that auxin biosynthesis inhibitors yucasin and L-Kynurenine remarkably inhibited the hypocotyl elongation of er-3 while yucasin shows a more severe inhibition to er-3 than Col-0. Relative expression of genes regulating auxin homeostasis and signaling, and GA homeostasis is less in er-3 than that in Col-0. Furthermore, genetic evidences show that ER regulated hypocotyl elongation is dependent of PHYTOCHROME B (PHYB). Overall, we propose that ER regulated shade avoidance by promoting hypocotyl elongation is PHYB-dependent and requires auxin and GAs.